CHALLENGE FOR ASEAN-CHINA FREE TRADE AGREEMENT ON INDONESIA EMPLOYMENT - Fatimah Riswati; Indro Warsito (Universitas Islam Indonesia, 2010)
This research analyzes the challenges for Indonesian economy towards the implementation ofASEAN-China Free Trade Area (ACFTA) especially on employment opportunity in Indonesia.Using regression technique, the labour cost and change in fix capital are statistically significant ininfluencing the employment opportunity. This result implies that ACFTA will challenge the Indonesiancompetitiveness due to increasing labour cost, while ACFTA also potentially increases capitalflow from China which has ambiguous impacts on labour absorption. The SWOT (Strength,Weakness, Opportunity and Threat) analysis recommends for Indonesian government to improvecomprehensive strategy of national industry to be more competitive to China products.Keywords: ACFTA, employment opportunity, structural equation modelJEL classification numbers: F13, F14, F15, F42